Efficiency of the technique of the training process of highly skilled bodybuilders of the mesomorphic type of constitution in the competitive period - Olexandr Tyhorskіy (Kharkiv State Academy of Physical Culture, 2016)
Purpose: foundation of efficiency of the technique of the training process of highly skilled bodybuilders in the competitive period. Material & Methods: 16 highly skilled bodybuilders of 22-30 years old participated in the research, the average body weight of sportsmen makes 872 - 1022 kg, which are included in the structure of the national team of Ukraine on bodybuilding. Methods: method of the theoretical analysis and generalization of literature, pedagogical observation, pedagogical experiment, method of mathematical statistics. Results: the comparative characteristic of the most often used techniques of the training process in bodybuilding is provided. The effective technique for highly skilled bodybuilders of the mesomorphic type of constitution, depending on the initial uniform of a sportsman at the beginning of the competitive period of training is developed and proved. Dependence of change of body weight of a bodybuilder on the training process is directed. Conclusions: on the effective training method, depending on microcycle of trainings in the competitive period precompetitive and competitive mesocycles (selection and main competitions), is offered the basis of the conducted research.